2017
DOI: 10.1038/srep45236
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative effects of ruthenium-based nucleolipidic nanoaggregates in human models of breast cancer in vitro: insights into their mode of action

Abstract: Looking for new metal-based anticancer treatments, in recent years many ruthenium complexes have been proposed as effective and safe potential drugs. In this context we have recently developed a novel approach for the in vivo delivery of Ru(III) complexes, preparing stable ruthenium-based nucleolipidic nanoaggregates endowed with significant antiproliferative activity. Herein we describe the cellular response to our ruthenium-containing formulations in selected models of human breast cancer. By in vitro bioscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(109 citation statements)
references
References 66 publications
6
101
0
Order By: Relevance
“…In order to verify the antiproliferative efficacy of the nucleolipid-or aminoacyl lipid-based Ru(III) complexes inserted in POPC-and DOTAP-based formulations, detailed investigations on their in vitro bioactivity were performed in comparison with naked AziRu [77,79,100,[105][106][107]110,134]. A selected panel of human and non-human cancer cell lines was chosen, particularly focusing on cells of different histopathological origin and widely used in anticancer research due to their replicative potential and malignancy, such as MCF-7 (human breast adenocarcinoma cell line), WiDr (human epithelial colorectal adenocarcinoma cell line), HeLa (human cervical cancer cells) and C6 (tumour rat glioma cells) [134][135][136]. In parallel experiments, some of these formulations were also tested on normal cell lines, such as L6 (rat muscle cells) and HaCaT (human keratinocytes cells), representing useful models to assess possible biological effect on healthy cells [137].…”
Section: In Vitro Bioactivitymentioning
confidence: 99%
“…In order to verify the antiproliferative efficacy of the nucleolipid-or aminoacyl lipid-based Ru(III) complexes inserted in POPC-and DOTAP-based formulations, detailed investigations on their in vitro bioactivity were performed in comparison with naked AziRu [77,79,100,[105][106][107]110,134]. A selected panel of human and non-human cancer cell lines was chosen, particularly focusing on cells of different histopathological origin and widely used in anticancer research due to their replicative potential and malignancy, such as MCF-7 (human breast adenocarcinoma cell line), WiDr (human epithelial colorectal adenocarcinoma cell line), HeLa (human cervical cancer cells) and C6 (tumour rat glioma cells) [134][135][136]. In parallel experiments, some of these formulations were also tested on normal cell lines, such as L6 (rat muscle cells) and HaCaT (human keratinocytes cells), representing useful models to assess possible biological effect on healthy cells [137].…”
Section: In Vitro Bioactivitymentioning
confidence: 99%
“…NPMBC inhibit the growth of TNBC cells better than non-TNBC cells [66]. Furthermore, NPMBC of which effects are dose- [49,53,55,67] and time- [63,67] dependent could be more cytotoxic than platinum-based drugs [52,53,57,58,68]. For example, Biancalana et al [57] observed that ruthenium complexes have good cytotoxic activity, with IC 50 values substantially lower than the values obtained with cisplatin on MDA-MB-231 cells.…”
Section: Suppression Of Cancer Cell Viability In Association With Thementioning
confidence: 99%
“…Furthermore, a study suggests that NPMBC could also inhibit angiogenesis [55]; however, because of scarce evidence, no definitive conclusion can be drawn on the role of these compounds in the regulation of blood vessel formation. In any case, it is thought that NPMBC are frequently multi-targeted and attack different biochemical pathways simultaneously [53,66,68], sometimes in a synergic way [37,62]. Cellular studies constitute an important step in the development of drugs; however, demonstrating efficacy in suitable animal models and validating cellular observations in vivo are a condition sine qua non for clinical trials investigating potential anticancer agents.…”
Section: Anticancer Effects Of Non-platinum Mbc (Npmbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…If trypan blue is detected, the instrument also accounts for the dilution and shows live cell count and percent viability. Total counts and live/dead ratio from random samples for each cell line were subjected to comparisons with manual hemocytometers in control experiments [29].…”
Section: Bioscreens In Vitromentioning
confidence: 99%